Gliniane przedmioty zoomorficzne ze stanowiska w Korczowej 22, pow. jarosławski - Jabłkowski, Michał (Muzeum Okręgowe w Rzeszowie, 2021)
During the motorway excavations carried out in 2010 in Korczowa, Jarosław dist., site 22, two zoomorphic items made of clay were discovered. These are: a fragment of a pendant and a fragment of a figurine. Figurative representations discovered at archaeological sites are associated with all possible forms of art. They are interpreted as objects of cult significance, children’s toys or manifestations of the magic sphere. The popularity of these representations and the influences of the „Eastern” cultures, especially the forest-stepped zone of the Scythian cultural circle, on the Tarnobrzeg Lusatian culture suggest that both the pendant and the figurine from site 22 in Korczowa should be associated with aforementioned cultural provenance.

In 2010, in connection with the planned construction of the A4 motorway, the Radymno-Korczowa junction, rescue excavations were undertaken, which provided the discovery of two clay zoomorphic objects, which are the subject of the article. These are: a fragment of a small, solid, longitudinal and cylindrical zoomorphic pendant and a miniature, fragmentarily preserved zoomorphic figurine. Figural art is rare in the Tarnobrzeg Lusatian culture. In the archaeological literature, this category of artefacts is dated from IV period of the Bronze Age to the Hallstatt period. The article shows that the most analogies can be found to the east of the area occupied by the Tarnobrzeg Lusatian culture. A common feature of all figural representations is the schematicism and simplicity of their performance as well as the dominance of images of farm animals. Figural art discovered in archaeological sites is identified with all forms of art. Such items are interpreted as objects of cult significance, children’s toys or manifestations of the magic sphere. The popularity of these representations and the influence of the „Eastern” cultures, especially the foreststepped zone of the Scythian cultural circle, on the Tarnobrzeg Lusatian culture suggest that both the pendant and the figurine uncovered at the site 22 in Korczowa should be associated with this cultural provenance.
Clay zoomorphic items from the site at Korczowa 22, Jarosław dist.
Keywords: Korczowa; Tarnobrzeg Lusatian culture; figural art; early Iron Age; Bronze Age; south-eastern Poland